Early development and feeding ability of yellow seahorse, Hippocampus kuda (Bleeker 1852), using selected live foods during critical life phase - Teh, Jun Chin (2017)
Low survival remains a significant hurdle in the nursery culture of yellow seahorse Hippocampus kuda. To potentially improve the survival and growth of H. kuda culture, their early feeding ability which deduced from the development of external and internal morphology, ontogeny and changes of digestive enzyme activities, as well as the effects of selected live foods, specifically during the critical phase of first 10 days were evaluated. The external morphology of newborn H. kuda was examined by scanning electron microscope (SEM) while their morphological development from 0 to 9 day-after-birth (DAB), both externally and internally, was inspected using the light microscope and analysed via histological approach. Despite the presence of some premature newborns with yolk sac attached to their bodies, normal H. kuda newborns had no external yolk sac and were able to swim freely and feed independently. The mouth gape size and mouth area increased from 0.26 to 0.53 mm and 0.070 to 0.165 mm2, respectively. The head length to snout length (H:S) ratio remained similar at 2.2 throughout the growth of H. kuda juveniles while the tail length to head length (T:H) ratio increased from 1.3 to 2.0 as the juvenile developed. The digestive system of H. kuda juveniles consisted of a snout, straight intestinal tube with an opened anus, as well as a gallbladder, liver and pancreas. No stomach was observed. Internal yolk globules were found in newborn H. kuda but were depleted by 1 DAB. Although the juvenile height and intestine length increased with the age, the relative intestine length remained similar at 0.30. Ontogeny development and activity of trypsin and chymotrypsin in H. kuda juveniles during the first 10 days and changes of digestive enzyme activities before and after feeding were evaluated using biochemical assays. Both the specific and total trypsin activities showed a similar trend where the activities were higher on 0–3 DAB, lower on 5 DAB and then slightly increased from 7 to 9 DAB. Meanwhile, the specific and total chymotrypsin activities were low on 0 DAB, increased on 1–3 DAB, before decreasing and remaining low from 5 to 9 DAB. The trypsin to chymotrypsin (T:C) ratio was highest on 0 DAB but dropped drastically on the following day and remained low until the end of experiment. However, the digestive enzyme activities became slightly higher after feeding on live food organisms. On the other hand, effects of different feeding regimes on H. kuda juveniles were investigated via two separate feeding trials. In Experiment 1, three feeding regimes (i) rotifers (20 ind mL-1), (ii) Artemia nauplii (4 ind mL-1), and (iii) a mixture of rotifers (15 ind mL-1) and Artemia nauplii (1 ind mL-1) were tested on H. kuda juveniles from 0 to 9 DAB. Prey consumption and heights of seahorses were measured every second day, while the survival and specific growth rate (SGR) were calculated after 9 DAB. A total mortality was observed among seahorses on 3 DAB and 5 DAB when only rotifers or Artemia were provided, respectively. The survival of seahorses fed the mixed live foods was 60% with a SGR of 6.3% d-1. Larger Artemia were selected over smaller rotifers as H. kuda juveniles developed. Strong positive correlations were found between the consumption of larger Artemia and the mouth gape size (r = 0.8551, P<0.05), and mouth area (r = 0.8509, P<0.05), but the consumption of smaller rotifers was negatively correlated to either the mouth gape size (r = -0.8345, P<0.05) or mouth area (r = -0.8194, P<0.05) of H. kuda juveniles from 3 to 9 DAB. In Experiment 2, newborn seahorses were initially fed a mixture of rotifers (15 ind mL-1) and Artemia nauplii (1 ind mL-1), followed by either additional (i) fish oil emulsion enriched Artemia metanauplii (0.5 ind mL-1) or (ii) copepods Oithona simplex (0.5 ind mL-1) from 3 DAB onwards. The introduction of copepods significantly (P<0.05) improved the SGR of H. kuda to 8.1 % d-1 compared to 6.8 % d-1 without copepod, although the survival was similar. Overall, the results indicated some progressive morphological changes along with a transition from partial lecithotrophy to full exogenous feeding in H. kuda juveniles during the first 10 days. The limited digestive capacity of H. kuda juveniles could have compensated by the autolysis of live food organisms. A feeding regime consisted of rotifers and Artemia nauplii mixture was suitable for H. kuda juveniles in terms of survival during this critical phase. To enhance growth, O. simplex should be used. These findings provided important knowledge to further improve the culture technique and perhaps development of an artificial feed for H. kuda species.